Optimization of Plant Growth Regulators for Tobacco Anther Culture Regeneration - Mohammad Nur Khozin; Imam Aditya Agung Mulyono; Didik Pudji Restanto; Aran Patarapuwadol; Iryono Iryono (Universitas Panji Sakti, 2026)
Tobacco is one of the most important plantation crops and is used as raw material by the cigarette industry. Improvements in the quantity and quality of tobacco crops are needed, one of which can be achieved by using superior hybrid varieties. However, the production of hybrid varieties requires pure-line plants, which are generally produced through conventional methods that take approximately 7–8 generations. Anther culture has emerged as an alternative method to accelerate the production of pure-line plants within 1–2 generations by using haploid plants. Although several studies have investigated the effects of auxins and cytokinins on anther culture in Solanaceae species, the optimal combination of 2,4-D and Kinetin for tobacco (Nicotiana tabacum L.) anther culture regeneration remains unclear. Therefore, this study aimed to optimize the combination of these plant growth regulators to improve regeneration efficiency in tobacco anther culture. The success of anther culture can be enhanced by using Plant Growth Regulators (PGRs) such as 2,4-D and Kinetin. This study aimed to determine the optimal concentration of 2,4-D and Kinetin for regenerating tobacco anther culture explants. The experiment was designed using a completely randomised design (CRD) with two factors: 2,4-D (0, 0,1, 1, and 2 mg/L) and Kinetin (0, 0,1, 0,2, and 0,4 mg/L). The interaction between 2,4-D and Kinetin significantly affected swelling initiation, callus initiation, and callus formation (P < 0.05). The D1K3 treatment (0.1 mg L⁻¹ 2,4-D + 0.4 mg L⁻¹ Kinetin) produced the fastest swelling initiation (3.67 DAI) and callus initiation (28.33 DAI), whereas D3K3 produced the highest callus formation (73.33%). Kinetin at 0.4 mg L⁻¹ significantly accelerated shoot (98 DAI) and root initiation (105 DAI). These findings demonstrate that optimizing the balance between auxin and cytokinin is essential for improving tobacco anther culture regeneration and provide useful information for doubled haploid production. However, a single application of Kinetin produced optimal effects on explant regeneration, resulting in the emergence of shoots and roots.